Wounded butterflies with heavy wings: a comparison of female characters in the theater of Federico García Lorca and Cao Yu - Bai, Yue (Estudios Complutenses de Asia Oriental, 2025)
Federico García Lorca and Cao Yu represent two outstanding playwrights in the world theater. Both have bequeathed to the present day works that stand out for their reflection on the life and society at the time, of which the creation of numerous unique characters is also appreciated. Through a close reading, it is easy to discover in them the special attention paid to the characterization of female characters. And due to the coincidence in the era that Lorca and Cao Yu lived, their feminist theaters show great similarities. They criticized the social darkness, and tried to find a way out for the women. By means of a comparison between the female characters of both, we can deeply understand the differences in their concepts about the women and their circumstances. From here it will be possible to address the particularity of the two when dealing with the female figures and their surrounding society.